Comparative antiplaque and antigingivitis effectiveness of tea tree oil mouthwash and a cetylpyridinium chloride mouthwash: A randomized controlled crossover study - Betul Rahman; Sausan Alkawas; Elaf Al Zubaidi; Omar I Adel; Nuha Hawas (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of this study was to compare the antiplaque and antigingivitis effects of a mouthwash containing tea tree oil (TTO) with a cetylpyridinium chloride (CPC) mouthwash. Materials and Methods: This was a randomized 4 × 4, controlled, cross-over, involving 20 healthy volunteers in a 5-day plaque re-growth model. Test mouthwashes were TTO (Tebodont® ) and a mouthwash containing CPC 0.05% (Aquafresh® ). A 0.12% chlorhexidine (CHX) mouthwash (Oro-Clense® ) was used as positive and colored water (placebo [PLB]) as negative controls. Gingival bleeding index (GBI) and plaque index (PI) scores were recorded before and after each test period. Test periods were separated with 2 weeks washout period. Results: All four mouthwashes significantly (P < 0.001) reduced the GBI scores when compared to the baseline GBI scores. There was no significant difference between PLB and active mouthwashes in the GBI scores. CHX and CPC mouthwashes were found more effective in reducing the PI scores than TTO and PLB mouthwashes. There was no significant difference in PI scores of CHX and CPC mouthwashes. Conclusion: 0.05% CPC mouthwash can be an alternative to CHX mouthwash since it is alcohol free and found as efficient as CHX in dental plaque reduction with lesser side effects. More studies are needed to test antigingivitis effects of the mouthwashes used in this study, preferably without initial scaling and polishing.